BMP4 and FGF3 haplotypes increase the risk of tendinopathy in volleyball athletes - Salles, J. I.; Amaral, M. V.; Pinheiro Aguiar, D.; Lira, D. A.; Quinelato, V.; Bonato, L. L.; Leite Duarte, M. E.; Rezende Vieira, A.; Casado, P. L. (Journal of Science and Medicine in Sport, 2014)
To investigate whether genetic variants can be correlated with tendinopathy in elite male volleyball athletes. Design: Case-control study. Methods: Fifteen single nucleotide polymorphisms within BMP4, FGF3, FGF10, FGFR1 genes were investigated in 138 elite volleyball athletes, aged between 18-35 years, who undergo 4-5 hours of training per day: 52 with tendinopathy and 86 with no history of pain suggestive of tendinopathy in patellar, Achilles, shoulder, and hip abductors tendons. The clinical diagnostic criterion was progressive pain during training, confirmed by magnetic resonance image. Genomic DNA was obtained from saliva samples. Genetic markers were genotyped using TaqMan real-time PCR. Chi-square test compared genotypes and haplotype differences between groups. Multivariate logistic regression analyzed the significance of covariates and incidence of tendinopathy. Results: Statistical analysis revealed participant age (p = 0.005) and years of practice (p = 0.004) were risk factors for tendinopathy. A significant association between BMP4 rs2761884 (p = 0.03) and tendinopathy was observed. Athletes with a polymorphic genotype have 2.4 times more susceptibility to tendinopathy (OR = 2.39;95%CI = 1.10-5.19). Also, association between disease and haplotype TTGGA in BMP4 (p = 0.01) was observed. The FGF3 TGGTA haplotype showed a tendency of association with tendinopathy (p = 0.05), and so did FGF10 rs900379. FGFR1 showed no association with disease. Conclusion: These findings indicate that haplotypes in BMP4 and FGF3 genes may contribute to the tendon disease process in elite volleyball athletes.